1981
DOI: 10.1093/oxfordjournals.aje.a113105
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure and 17-Year Cancer Mortality in the Western Electric Health Study1

Abstract: A positive association between elevated blood pressure and risk of death from cancer has been observed in four long-term prospective studies. In the Western Electric Health Study, the relationship was specific to death from renal cell carcinomas and epidermoid cancers of the head and neck. The relationship with epidermoid head and neck cancer was indirect, resulting from the effects of alcohol consumption on both blood pressure and on risk of this cancer. The relationship with kidney cancer was probably due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…The association between hypertension and RCC is unlikely to be the consequence of renal cancer as subjects who were diagnosed with hypertension 20 or more years before cancer diagnosis still experienced a statistically significant twofold elevation in risk. This is not a novel finding as numerous case-control and cohort studies have also observed this relationship (Raynor et al, 1981;Grove et al, 1991;Kreiger et al, 1993;Heath et al, 1997). Diabetes and stroke, which are known to be related to obesity and hypertension, were also associated with RCC risk in our study, but these associations disappeared after adjustment for obesity and history of hypertension.…”
Section: Discussionsupporting
confidence: 52%
“…The association between hypertension and RCC is unlikely to be the consequence of renal cancer as subjects who were diagnosed with hypertension 20 or more years before cancer diagnosis still experienced a statistically significant twofold elevation in risk. This is not a novel finding as numerous case-control and cohort studies have also observed this relationship (Raynor et al, 1981;Grove et al, 1991;Kreiger et al, 1993;Heath et al, 1997). Diabetes and stroke, which are known to be related to obesity and hypertension, were also associated with RCC risk in our study, but these associations disappeared after adjustment for obesity and history of hypertension.…”
Section: Discussionsupporting
confidence: 52%
“…25 Epidemiologically, there have been several prospective studies reporting hypertension as a significant risk factor for cancer. [6][7][8][9][10] Clinically, many investigators have reported observational studies suggesting a relation between hypertension and cancer in the past 20 years. 5 This relation is, however, not yet clearly confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…5 In fact, in some prospective cohort studies, a modest direct association between blood pressure levels and the overall risk of death from cancer has been reported. [6][7][8][9][10] In addition, two reports described a somewhat greater incidence of cancer among patients receiving treatment with a calcium antagonist than among others in the population studied. 11,12 Some investigators argued that this result may have been affected by confounding factors.…”
Section: Introductionmentioning
confidence: 92%
“…Desta forma, ainda que com uma amostra reduzida, não aleatória, observamos uma maior freqüência de tumores dos tratos digestivo, respiratório e genitourinário, localizações freqüentes de câncer ocupacional, por tratarem-se de áreas de entrada ou eliminação de agentes químicos cancerí-genos 7,8,14 .…”
Section: * Em Estudo Recentemente Realizado Pelo Departamento De Servunclassified